Enhanced recovery pathway for radical prostatectomy: Implementation and evaluation in a universal healthcare system - Abou-Haidar, Hiba; Abourbih, Samuel; Braganza, David; Al Qaoud, Talal; Lee, Lawrence; Carli, Franco; Watson, Deborah; Aprikian, Armen G.; Tanguay, Simon; Feldman, Liane S.; Kassouf, Wassim (Canadian Urological Association Journal, 2014)
Introduction: Enhanced recovery pathways are standardized, multidisciplinary, consensus-based tools that provide guidelines for evidence-based decision-making. This study evaluates the impact of the implementation of a clinical care pathway on patient outcomes following radical prostatectomy in a universal healthcare system. Methods: Medical charts of 200 patients with prostate cancer who underwent open and minimally invasive radical prostatectomy at a single academic hospital from 2009 to 2012 were reviewed. A group of 100 consecutive patients’ pre-pathway implementation was compared with 99 consecutive patients’ post-pathway implementation. Duration of hospital stay, complications, post-discharge emergency department visits and readmissions were compared between the 2 groups. Results: Length of hospital stay decreased from a median of 3 (interquartile range [IQR] 4 to 3 days) days in the pre-pathway group to a median of 2 (IQR 3 to 2 days) days in the post-pathway group regardless of surgical approach (p < 0.0001). Complication rates, emergency department visits and hospital readmissions were not significantly different in the pre- and post-pathway groups (17% vs. 21%, p = 0.80; 12% vs. 12%, p = 0.95; and 3% vs. 7%, p = 0.18, respectively). These findings were consistent after stratification by surgical approach. Limitations of our study include lack of assessment of patient satisfaction, and the retrospective study design. Conclusions: The implementation of a standardized, multidisciplinary clinical care pathway for patients undergoing radical prostatectomy improved efficiency without increasing complication rates or hospital readmissions.